Exposure to indoor air pollution and the cognitive functioning of elderly rural women: a cross-sectional study using LASI data, India - Manoj Dakua; Ranjan Karmakar; Papai Barman (BMC, 2022)
Abstract Background The majority of people in rural developing counties still rely on unclean and solid fuels for cooking, putting their health at risk. Adult and elderly women are most vulnerable due to prolonged exposure in cooking areas, and Indoor Air Pollution (IAP) may negatively impact their health and cognitive function. This study examines the effect of IAP on the cognitive function of middle-aged and elderly rural women in India. Methods The study utilized the data from the Longitudinal Ageing Study in India (LASI 2017-18, Wave-1). Bivariate analysis and multilevel linear regression models were applied to show the association between IAP and the cognitive abilities of rural women and results from regression were presented by beta coefficient (β) with 95% confidence interval (CI). Confounding factors such as age, education, health risk behaviours, marital status, monthly per capita consumption expenditure (MPCE), religion etc. were adjusted in the final model. Results The study found that 18.71 percent of the rural women (n = 3,740) lived in Indoor Air Pollution exposed households. IAP was significantly found to be associated with the cognitive functional abilities among the middle and older aged rural women. Middle and older aged rural women exposed to IAP had lower cognitive functional abilities than non-exposed women. Comparing to the non-exposed group, the cognitive score was worse for those exposed to IAP in both the unadjusted (β = -1.96; 95%CI: -2.22 to -1.71) and the adjusted (β = -0.72; 95%CI: -0.92 to -0.51) models. Elderly rural women from lower socioeconomic backgrounds were more likely to have cognitive impairment as a result of IAP. Conclusion Findings revealed that IAP from solid fuels could significantly affect the cognitive health of elderly rural women in India, indicating the need for immediate intervention efforts to reduce the use of solid fuels, IAP and associated health problems.